2020
DOI: 10.1111/bjh.16377
|View full text |Cite
|
Sign up to set email alerts
|

Advances in knowledge of inhibitor formation in severe haemophilia A

Abstract: Summary Anti‐drug antibody formation following factor VIII (FVIII) replacement therapy is the most important treatment‐related complication in patients with severe haemophilia A. A significant number of these antibodies show neutralising activity against FVIII and are referred to as FVIII inhibitors. Alloimmunity to FVIII, given the absence of endogenous circulating FVIII protein, may be predictable to some extent; however, only 30% of patients develop inhibitors. Genetic and environmental risk factors have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 123 publications
0
27
0
3
Order By: Relevance
“…Specifically, different glycosylation patterns could be the primary factor. [39] For example, it was concluded that a mannose receptor is involved in immune recognition of FVIII by antigen-presenting cells (APC), e.g., dendritic cells. [40] Our work and previous studies showed that N2118 at the C1 domain is primarily attached with high-mannose N-glycans in both pdFVIII and rFVIII, [23,24] suggesting a mechanism for FVIII internalizations by APC via the mannose receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, different glycosylation patterns could be the primary factor. [39] For example, it was concluded that a mannose receptor is involved in immune recognition of FVIII by antigen-presenting cells (APC), e.g., dendritic cells. [40] Our work and previous studies showed that N2118 at the C1 domain is primarily attached with high-mannose N-glycans in both pdFVIII and rFVIII, [23,24] suggesting a mechanism for FVIII internalizations by APC via the mannose receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The International Severe Acute Respiratory and Emerging Infection Consortium is developing a clinical trial protocol to investigate passive immunotherapy for severe acute respiratory and emerging infection. 54,59 Viral load by quantitative viral nucleic acid testing and viral antibody titers were found to be useful in defining the virologic and immunological kinetics that lead to improved clinical outcomes. It will be important to define the optimal plasma volume, number of doses, and quantitative neutralizing antibody titers to determine the optimal amount of antibody that is needed to effectively inhibit virus replication.…”
Section: Severe Acute Respiratory Syndromementioning
confidence: 99%
“…Plasma collection 14 days after resolution of symptoms provides the best likelihood of having high titers of anti-SARS-CoV-2 antibodies. 59 Convalescent plasma may be provided to patients with SARS-CoV-2 infections through one of three approval pathways: (1) Passive Immunity for COVID- 19 Lindholm et al 801 This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…The development of factor VIII (FVIII) neutralizing antibodies, known as inhibitor, is the most serious treatment-related complication for hemophilia A (HA) and is detected in 25%–30% of patients. 1 Inhibitor development is a multifactorial process involving genetic and non-genetic risk factors. Non-genetic risk factors include severe bleeding, infections, and vaccinations around the time of FVIII treatment based on the ‘danger theory’.…”
Section: Introductionmentioning
confidence: 99%